2010
DOI: 10.3109/10428190903580402
|View full text |Cite
|
Sign up to set email alerts
|

A phase II study of alemtuzumab, fludarabine, cyclophosphamide, and doxorubicin (Campath-FCD) in peripheral T-cell lymphomas

Abstract: The clinical course of peripheral T-cell lymphoma (PTCL) is usually aggressive and the prognosis unfavorable. Therefore, there is a need for improvement of treatment options. Patients with newly diagnosed (n = 27) or refractory/relapsed (n = 11) PTCL received a combination of alemtuzumab, fludarabine, cyclophosphamide, and doxorubicin. The overall response rate (ORR) was 61%, with a complete response rate of 39%. In newly diagnosed patients the ORR was 63%, the median overall survival 25.9 months, and progress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

2010
2010
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 23 publications
0
21
0
1
Order By: Relevance
“…The 55% of evaluable patients had PTCL-U, with an overall response rate of 61%, and a CR rate of 78% for previously untreated patients; however, regarding the survival a longer follow-up period is required. This study demonstrated that alemtuzumab can be combined with a chemotherapy regimen, nevertheless, haematological toxicity and cytomegalovirus reactivation remains the major limitations [96]. Others combination studies in PTCL in the same way as alemtuzumab with EPOCH or CHOP regimens are ongoing.…”
Section: Monoclonal Antibodies and Immunotoxinsmentioning
confidence: 87%
“…The 55% of evaluable patients had PTCL-U, with an overall response rate of 61%, and a CR rate of 78% for previously untreated patients; however, regarding the survival a longer follow-up period is required. This study demonstrated that alemtuzumab can be combined with a chemotherapy regimen, nevertheless, haematological toxicity and cytomegalovirus reactivation remains the major limitations [96]. Others combination studies in PTCL in the same way as alemtuzumab with EPOCH or CHOP regimens are ongoing.…”
Section: Monoclonal Antibodies and Immunotoxinsmentioning
confidence: 87%
“…Overall, there were 6 treatment-related deaths in the trial, including 2 patients who developed an EBV-associated lymphoproliferative disorder due to profound immunosuppression related to the combination of fludarabine and alemtuzumab. 14 Currently, there are 2 ongoing phase 3 trials in Europe comparing dose-dense CHOP-14 with CHOP-14 plus subcutaneous alemtuzumab in younger patients (Ͻ 60 years, ACT-1) and older patients (Ͼ 60 years, ACT-2). Both trials include growth factor support, and ACT-1 also includes HDC/ASCT in responding patients.…”
Section: Chop With Alemtuzumabmentioning
confidence: 99%
“…Alternative approaches to CHOP have been fl udarabine-containing regimens alone or a combination with the monoclonal anti-CD52 antibody Alemtuzumab for PTCL/L, especially in T-PLL [35,50]. Alemtuzumab has also been successfully combined with CHOP protocols [34,38,43].…”
Section: Immuno-chemotherapy In Ptcl/lmentioning
confidence: 99%